المسؤولية الجزائية عن افشاء السرية المصرفية - بن حضرية, اسامة; بن مبارك, هناء; بن مبارك, ياسمين (Universté ELOUEd-جامعة الوادي, 2023)
تتناول هذه الدراسة النظام القانوني للسرية المصرفية في التشريع الجزائري، وسيعتمد في الأساس على أسلوب تحليل النصوص التي عالجت السرية المصرفية وفق القواعد العامة في التشريعات الجزائرية إذ لا يوجد قانون خاص للسرية المصرفية في الجزائر. مع التركيز على النص العام وهو نص المادة (301) من قانون العقوبات الجزائري، وبيان مدى انطباقه على حريمة إفشاء السر المصرفي. وتقسم هذه الدراسة إلى مبحثين تتناول في المبحث الأول الإطار المفاهيمي السر المصرفي والأساس القانوني له ومصادر السرية المصرفية والأشخاص الملتزمون بالسر المصرفي والتركيز على الاستثناءات الواردة على هذا المبدأ، وفي الفصل الثاني فسيكون مدارا لبحث المسؤولية الجزائية المترتبة عن إفشاء السر المصرفي، من أركان الجريمة إلى العقوبات الجزائية، وأخيرا الخاتمة التي تتضمن النتائج والتوصيات والاقتراحات.Times New Roman (برنامج نصي معقد لعناوين)This study deals with the legal system of the financial privacy in the Algerian legislation. It depends mainly on text analysis method which treated the financial privacy according to the general rules in the Algerian legislations since there is not a specific law for the financial privacy in Algeria. It focuses on the general act which is the text of article number 301 of the Algerian penal code, and an indication of its applicability to the crime of disclosing financial privacy. This study has two parts. The first research part deals with the conceptual framework of financial privacy, its legal basis, the sources of the financial privacy as well as the committed persons to the financial privacy. Also, it focuses on the incoming exceptions on this principle. The second research part deals discussing the criminal responsibility resulting from the disclosure of the financial privacy, beginning with the elements of the crime to the penal punishments. Finally, the conclusion includes the results, recommendations and suggestions.
مذكرة ماستر
Keywords: مفهوم السرية المصرفية، جريمة افشاء السر المصرفي، التشريع الجزائري، العقوبات المقررة لها.: Conception of the financial privacy, crime of disclosing of the financial privacy, the Algerian legislation, penalties for the crime of disclosing the financial privacy